Enamel Surface Roughness after Debonding of Orthodontic Brackets and Various Clean-Up Techniques - Ahrari, Farzaneh (Tehran University of Medical Sciences, 2013)
OBJECTIVE: This study aimed to evaluate enamel roughness after adhesive removal using different burs and an Er:YAG laser. MATERIALS AND METHODS: The buccal surfaces of forty human premolars were sealed by two layers of nail varnish, except for a circular area of 3 mm in diameter on the middle third. The enamel surfaces were initially subjected to profilometry analysis and four parameters of surface irregularity (Ra, Rq, Rt and Rz) were recorded. Following bracket bonding and debonding, adhesive remnants were removed by tungsten carbide burs in low- or high- speed handpieces (group 1 and 2, respectively), an ultrafine diamond bur (group 3) or an Er:YAG laser (250 mJ, long pulse, 4 Hz) (group 4), and surface roughness parameters were measured again. Then, the buccal surfaces were polished and the third profilometry measurements were performed. RESULTS: The specimens that were cleaned with a low speed tungsten carbide bur showed no significant difference in surface irregularity between the different treatment stages (p>0.05). Surface roughness increased significantly after clean-up with the diamond bur and the Er:YAG laser (p<0.01). In comparison between groups, adhesive removal with tungsten carbide burs at slow- or high-speed handpieces produced the lowest, while enamel clean-up with the Er:YAG laser caused the highest values of roughness measurements (P<0.05). CONCLUSION: Under the study conditions, application of the ultrafine diamond bur or the Er:YAG laser caused irreversible enamel damage on tooth surface, and thus these methods could not be recommended for removing adhesive remnants after debonding of orthodontic brackets.